Territórios educativos de intervenção prioritária : breve balanço e novas questões - Isabel Ferreira; Ana Rita Teixeira (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2010)
The Territórios Educativos de Intervenção Prioritária (TEIP), created in 1996 on the basis of a policy of positive discrimination and giving priority to combat failure at school, were inspired by the politics of ZEP in France, the experiences of compensatory education developed in the U.S., the programs of ‘war on poverty’ and the British experience in the same season. This article seeks to reflect on the creation and implementation of TEIP by reviewing the literature on the theme